National Cultural Fostering Factors by M. Lukšienė Concept in Technology Curriculum: Basic Education Programs General Dimension - Valantinaitė, Ilona (Pedagogika, 2013)
This paper discusses the components of creation and cultural conception in prof. M. Lukšienė’s articles and the impact of her work on the Basic Education General Technology Programmes (2008). The professor justifies the importance to preserve and foster a culture in a continuously changing environment. Every person is born and matures in culture, later he changes, protects and creates it himself. In today’s information society, a fulcrum should be authenticity and the basis of values. Activity, which is derived from values, has the power of consciousness and truth; later it becomes a creative force. In order to pursue conscious and responsible society, it is advisable to begin with child’s education on the basis of values, emphasizing the significance of culture and its structure. Generally, authentic culture belongs to authentic people. The object of the research – the assumptions of cultural enhancement in technology lessons according to M. Lukšienė’s conception of culture. The goal – to justify technological education as an enhancement factor of national culture in the articles of M. Lukšienė. The research methods: the qualitative analysis of scientific sources and educational documents. The performed analysis on M. Lukšinė’s written texts and works has formed the basis for grouping the following analysis into main categories. Such as cultural construct, cultural enhancement on personal and organisational level, and in terms of time: the old and new. The analysis is represented in a table format. According to M. Lukšienė’s conception of culture, language, ethnicity and values are the main contact points with the Basic Education General Technology Programmes (2008). In the process of understanding and recognising the cultural components, there are high standards for a technology teacher who could convey a perception of cultural components as being one of the essential values in humans to his students. By preserving person’s inner culture, we will be able to preserve the culture of a whole nation. Thus there is a need to take responsibility of our own activity / inactivity, choices, and constantly recognise the fundamental truth – culture in human and human in culture. Every component and measure, discussed by M. Lukšienė, fids a clear response in the General Education Technology Programmes (2008) and, possibly, in technology lessons too. Today’s programmes in each technology session allow weaving the old and new, lay innovation on the basis of values and be measured by authenticity. It also enables to act inventively, not to lose for one moment the very self, read the works and ornaments of folk art, and utter a wisdom by respecting every word of a native language. Moreover, the professor advises to talk to each other only “as being a sage” and suggests protecting every person in our own culture. M. Lukšienė has formed the strong foundations for fostering nationality and culture whereas the Basic Education General Technology Programmes (2008) allow continuing the professor’s started works and developing her cherished ideas.